Penetapan Strategi Pemuliaan untuk Mendukung Pengembangan Malapari (Pongamia pinnata L.) sebagai Penghasil Biofuel - Jayusman, Jayusman (Universitas Sebelas Maret, 2018)
Malapari (PongamiapinnataL.) is widespread in Indonesia and is a highly prospective priority species to support the national biofuel development program. The P. pinnata development program as one of the alternative biofuel producing species has begun at BBPPBTH through exploration and collection of genetic material from various provenances spread across Indonesia. Evaluation and analysis of the best provenances based on the yield of crude oil has been completed. To meet the needs of short-term seeds in 2018 has been the development of provenance seed sources using genetic material based on the best provenance. Another important urgent stage is the establishment of a P. pinnata breeding strategy that will be a provide direction to productivity improvement activities. Breeding strategies are crucial to optimize genetic acquisition effectively. Initiating the preparation of P. pinnata breeding strategies in the early stages, evaluating the fulfillment of elements of a breeding strategy that includes (1) the setting of breeding objectives, (2) preparation of the basic population and breeding population, (3) the selection methode, (4) the genetic test and 5) relationship management. Based on preliminary evaluation, there are still elements of breeding strategies that have not been met, such as the presence of basic populations that have wide genetic diversity, the selection of the most appropriate selection mothode, the implementation of genetic testing and the implementation of relationship management. For resource and time efficiency the focus and priority of P. pinnata breeding activities of the next phase should be directed to meet the four elements. In addition, attention to the determinants of P. pinnata breeding strategies should also receive attention such as the mastery of reproductive biology, understanding the role of additive and non-additive genes, hybrid potentials as well as interactions of genetic factors and location of development.